The Impact of Tourism Development on the Income of the Pandesari Village Community, Pujon District, Malang Regency - Prasetyo, Galang; Maryunani (Journal of Development Economic and Social Studies, 2026)
Tourism is one of the main industrial sectors in Indonesia. Some of them are located in Malang Regency, East Java. The various tourism potentials provide benefits for both urban and rural areas. One such area is Pandesari Village, known for its family tourism due to its significant tourism potential. Tourism in the Pandesari Village area also plays a role in raising environmental awareness and nature conservation. The development of tourism in this village has a significant impact on the income of the local community. Therefore, this study aims to examine the impact of tourism development on the income of the residents of Pandesari Village, Pujon District, Malang Regency, and the factors influencing their income. This research employs a quantitative approach using primary data obtained directly from the research subjects. The results of this study are expected to provide valuable recommendations for sustainable tourism development in the village. This research can also be used as a reference for similar studies in other regions.